Classes of food additives in food products sold in Mauritius. Issue 5 (3rd June 2019) - Etwaroo, Dhamawatee Harnarun; Goburdhun, Dayawatee; Ruggoo, Arvind
Abstract : Purpose: Food additives are a group of substances added deliberately to foods to improve their organoleptic properties and stability, extend their shelf life and retain their nutritional value. The purpose of this paper is to identify the most frequently used classes of food additives and the food categories which contain the highest number of classes of additives. Design/methodology/approach: A market survey was carried out in hypermarkets and shops where the original labels of 629 food products (195 local and 434 imported) were examined for presence of food additives. Principal component analysis (PCA) was used to explore the association between food category and classes of additives, and a χ 2 test was performed to establish any association between product origin and the number of classes of food additives. Findings: In sum, 75 per cent of food samples surveyed contained at least one class of food additive. The food categories which contained the highest number of classes of food additives across the group were: snacks (12 classes), biscuits and cakes (11 classes), fish products (11 classes) and soft drinks (10 classes). The most common classes of additive used were acidity regulator, colour and preservative. χ 2 test revealed a significant association ( χ 2 = 8.28, p < 0.05) between the origin and number of classes of food additives, and the PCA showed that biscuits were associated with raising agent, candies and snacks with colour, fruit drinks and soft drinks with acidity regulator, mayonnaise with thickener and meat products with preservative. Research limitations/implications: The food products were sourced only from retailers selling labelled food products. Originality/value: This novel study provides a basis for determining compliance of food products to the National Food Regulations.